2019
DOI: 10.1016/j.heliyon.2019.e02393
|View full text |Cite
|
Sign up to set email alerts
|

Screening of bacteriocin associated genes of Streptococcus uberis strains

Abstract: A wide variety of contagious and environmental bacteria can cause bovine mastitis worldwide. Antibiotic therapy is currently used for the treatment of the disease, although its intensive use leads to the emergence of resistant strains. Bacteriocins arise as potential antibacterial option for mastitis treatment. The aim of this work was to analyze bacteriocin associated genes as Streptococcus uberis ubericin A (ubaA), ubericin A immunity protein (ubaI), uberolysin A (ublA), Lantibiotic nisin-U (nsuA and nsuB) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…In cattle, the most common target group for the use of bacteriocins includes pathogens responsible for the infection of mammary glands [ 147 ]. Godoy-Santos et al [ 148 ] showed an inhibitory effect of bovicin, a bacteriocin produced by Streptococcus equinus , against most Gram-positive isolates from mastitis but not against Gram-negative strains, including E. coli .…”
Section: Antimicrobial Peptidesmentioning
confidence: 99%
See 1 more Smart Citation
“…In cattle, the most common target group for the use of bacteriocins includes pathogens responsible for the infection of mammary glands [ 147 ]. Godoy-Santos et al [ 148 ] showed an inhibitory effect of bovicin, a bacteriocin produced by Streptococcus equinus , against most Gram-positive isolates from mastitis but not against Gram-negative strains, including E. coli .…”
Section: Antimicrobial Peptidesmentioning
confidence: 99%
“…The research conducted by Carson et al [ 149 ] confirmed that bacteria that are the main cause of mastitis (non- Aureus staphylococci ) may also be an important group of producers of bacteriocin that effectively inhibits not only animal-origin S. aureus but also human-origin methicillin-resistant S. aureus strains (MRSA). Lasagno et al [ 147 ] showed the presence of genes encoding more than one bacteriocin in Streptococcus uberis strains isolated from mastitis; moreover, these strains showed inhibitory activity against other species of bacteria causing mastitis, especially coagulase-negative staphylococci.…”
Section: Antimicrobial Peptidesmentioning
confidence: 99%
“…Previous studies have used PCR screening to investigate the distribution of biosynthetic gene clusters associated with bacteriocin production (Lasagno et al . 2019; Sabino et al . 2019; Campanero et al .…”
Section: Discussionmentioning
confidence: 99%
“…Virulence genes screened by PCR DNA extraction was carried out according to Lasagno et al (2019). The presence of virulence genes, gapC, hasABC, lbp, pauA and sua was assayed by PCR.…”
Section: Intracellular Survival Assaymentioning
confidence: 99%